2020
DOI: 10.1515/ijnsns-2019-0227
|View full text |Cite
|
Sign up to set email alerts
|

A parallel hybrid implementation of the 2D acoustic wave equation

Abstract: In this paper, we propose a hybrid parallel programming approach for a numerical solution of a two-dimensional acoustic wave equation using an implicit difference scheme for a single computer. The calculations are carried out in an implicit finite difference scheme. First, we transform the differential equation into an implicit finite-difference equation and then using the alternating direction implicit (ADI) method, we split the equation into two sub-equations. Using the cyclic reduction algorithm, we calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The paper does not consider the problems of the Navier-Stokes equation in doubly connected areas. In [23], a hybrid implementation was developed using the MPI, OpenMP and Compute Unified Device Architecture (CUDA) technologies and showed that this implementation gives good results.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The paper does not consider the problems of the Navier-Stokes equation in doubly connected areas. In [23], a hybrid implementation was developed using the MPI, OpenMP and Compute Unified Device Architecture (CUDA) technologies and showed that this implementation gives good results.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The modern world and information systems are data-driven, generated in huge quantities every day [1]. Therefore, to obtain truly valuable results in modern realities in industrial, business or scientific problems, it is very important to be able to effectively process the big data available to us, using the tools available for this, and some scientists use parallel data processing on many computing nodes [2].…”
Section: Introductionmentioning
confidence: 99%